Synthesis of Na-CMC Modified Cellulose Membrane From Water Hyacinth (Eichhornia Crassipes) Rods Against Cr (VI) Metal Adsorption - Nafi'ah, Rohmatun; Rosyidah, Siti (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2021)
Metal ion Cr (VI) is a type of heavy metal waste that is dangerous, so we need a method to reduce the level of pollution. The separation method using a cellulose membrane is an effective method to reduce the level of Cr (VI) metal pollution, by utilizing natural materials such as water hyacinth plants which are known to contain high enough cellulose. The purpose of this study was to determine the effect of concentration variations with time variations on the adsorption capacity of Cr (VI) metal ions from Na-CMC modified cellulose membranes from water hyacinth (Eichhornia crassipes) stems. This research uses experimental research methods, the steps that have been carried out are sample treatment, extraction, bleaching, hydrolysis, Na-CMC modified cellulose membranes. Data analysis was performed by sample characterization test using the FTIR Spectroscopy method and for metal content analysis using the Atomic Absorption Spectrophotometer (AAS) method. The results showed that there was an effect of concentration variations and time variations on the adsorption capacity of Cr (VI) metal ions. At the concentration variation with the largest adsorption capacity of 1.24 mg/gram occurred at a concentration of 30 mg/L and at the time variation the largest adsorption capacity of 0.917 mg/gram occurred at 30 minutes. The results respectively of FTIR showed functional groups O-H, C-H, and C-O in non-modified cellulose and there was no significant effect after the addition of Na-CMC, as evidenced by the similar FTIR spectrum without any shift or new peaks appearing.Â